Mathematical Cryptanalysis of Personalized Info ation Encryption Using FCG Signals with Chaotic Functions - Gencoglu, Muharrem Tuncay (Ieee, 2017)
The chaotic system and cryptography have some common features. Due to the close relationship between chaotic system and cryptosystem, researchers try to combine the chaotic system with cryptosystem. In this study, security analysis of an encryption algorithm which aims to encrypt the data with ECG signals and chaotic functions was performed using the Logistic map in text encryption and Henon map in image encryption.In the proposed algorithm, text and image data can be encrypted at the same time.In addition,ECG signals arc used to determine the initial conditions and control parameters of the chaotic functions used in the algorithm to personalize of the encryption algorithm. In this cryptanalysis study, the inadequacy of the mentioned process and the weaknesses of the proposed method have been determincd.Encryption algorithm has not sufficient capacity to provide necessary security level of key space and secret key can be obtained with only one plaintext/ciphertext pair with chosen-plai ntext attack.
2017 International Conference on Computer Science and Engineering (UBMK) -- OCT 05-08, 2017 -- Antalya, TURKEY
Keywords: chaos; cryptography; Electrocardiogram; Cryptanaksis; chosen -plain text attack